Effective removal of contaminants from biotreated leachate by a combined Fe(III)/O3 process: Efficiency and mechanisms. (10th December 2020) - Wang, Ya-nan; Wang, Huawei; Wu, Yajing; Sun, Yingjie; Gong, Zhaoguo; Liu, Keqiong; Tsang, Yiu Fai; Zhan, Meili
Abstract: Refractory organics and toxic metals are still the main contaminants in the landfill leachate effluents from membrane bioreactors (MBRs) (expressed as biotreated leachate). In this study, a combined Fe(III)/O3 process was employed for the removal of multiple contaminants from a biotreated leachate in Qingdao city, China. Effects of ozone dose, Fe(III) dose, initial pH and reaction time on the removal efficiency of refractory organics were systemically investigated. The degradation mechanisms of organics were discussed based on a combination of microscopic and spectroscopic analyses. In addition, the removal efficiency of toxic metals from biotreated leachate was also performed. The results indicated that refractory organics in the leachate were effectively degraded in the Fe(III)/O3 system. The removal efficiencies of COD, TOC and UV254 were 80.23%, 74.85% and 85.01%, respectively, under the following optimum operational conditions: O3 dose of 100 mg/min, Fe(III) dose of 6 g/L, reaction time of 25 min, and initial pH of 6.5. At this conditions, the effluent COD and BOD5 were satisfied the discharge standard of pollutants to open seas in Qingdao city, China. Spectroscopic analysis suggested that refractory organics in the leachate were effectively destroyed and mineralized during the Fe(III)/O3 process. Additional, in-situ formation of Fe-containing particles (mainly as Fe(OH)3 ) contributed to the adsorptive removal of organics and toxic metals (i.e., Cu, Ni, As, Cr, Pb and Zn). Graphical abstract: Image 1 Highlights: 80.23% of COD and 74.85% of TOC are eliminated at the optimum conditions. Refractory organics and toxic metals are effectively removed by the Fe(III)/O3 treatment. In-situ formation of Fe(OH)3 contributes to the adsorptive removal of organics. Fe(III)/O3 is an efficient way for removing contaminants from biotreated leachate.